FAKTOR AYAH DAN IBU YANG BERKONTRIBUSI TERHADAP MUNCULNYA GEJALA PERILAKU DISRUPTIF REMAJA - Syakarofath, Nandy Agustin; Subandi, Subandi (Jurnal Psikologi, 2019)
Disruptive behavior according to DSM 5 is a pattern of behavior that violates the rights of others, aggression, property destruction and or that leads individuals to experience significant conflicts with violations of social norms or authority figures. This study aims to examine the significance of two factors derived from the family towards the emergence of disruptive behavior that are the family expressed emotion and perceived of parentchild relationships. There are 237 teenagers was participated in this study (aged 15-18 years old) who lived with their parent obtained from the scaling of SDQ, LEE and PACQ. The result of the regression indicated the two predictors explained 5,3% of variance (adjusted R2 = .053, F(3.235) = .013, p<.05). The implications of this study are the family expressed emotion and perceived of parent-child relationships are two factors that can contributed to the emergence of disruptive behavior symptoms in adolescent, although if analyzed separately perceived of parent-child relationships towards a mother has no effect.Â Â